Prime Minister's Decree No. 47 of the Year 2020 Concerning the Rules, Controls and Procedures of Offering Heavy Industry Licenses and Others to Investors = قرار مجلس الوزراء رقم 47 لسنة 2020 بشأن قواعد وضوابط وإجراءات طرح تراخيص الصناعات الثقيلة وغيرها للمستثمرين - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic